Road safety development evaluation in the ASEAN region - Zhu, Zhiyuan (Transactions on Economics, Business and Management Research, 2024)
Catch a glimpse of the serious and severe traffic situation, it is conceivably that the systematic assessment of road safety in the dimension of national level is indispensable and extremely essential. In this connection, the main body of the article proposed a set of evaluation measure based on Entropy-TOPSIS-RSR. In addition, the reliability and scientific nature of this method were tested through robustness analysis. In conclusion, the proposal of the measure will definitely provide a scientific decision-making basis for the formulation of action plans and resource allocation in Southeast Asia in the future.